La estructura familiar y su incidencia en el desarrollo socio-afectivo de los niños y niñas de primer año de educación básica de la unidad educativa fiscal mixta 29 de Mayo; de la ciudad de Macas. Periodo lectivo 2013-2014 - Jurado Villacis, Angela Veronica (2014)
This research is "FAMILY STRUCTURE AND ITS IMPACT ON SOCIAL EMOTIONAL DEVELOPMENT OF SCHOOL CHILDREN, FIRST DEGREE OF EDUCATION BASIC EDUCATION FISCAL UNIT MIXED "29 DE MAYO "; CITY MACAS LECTIVO PERIOD 2013-2014", the same as has been done according to the provisions of the Regulation of Academic Board of the National University of Loja. Raised the overall objective: To present the importance of family structure and its impact on their Socio- Affective Development of children Educational Joint Fiscal Unit "29 de Mayo"; City Macas semester 2013 - 2014.Los methods used for this research work were: Scientist, Inductive- Deductive; Synthetic Analytical and Statistical Model; that served them help achieve efficiency of research. The techniques and instruments used were directed to Survey Parents or guardians of children, in order to know about the Family Structure; and a test to determine the level of Socio- Affective children. From the survey of parents, it is concluded that 67 % of parents of children Educational Joint Fiscal Unit "29 de Mayo" belong to a nuclear family, 13% to the patriarchal family and with the same percentage monkey parental family and 7% for the reconstructed family. With the application of the test Ebbe Leon Gross 87% of children of the Joint Fiscal Education Unit "29 de Mayo" have a Satisfactory standard in its Socio- Affective Development so that parents and teachers need not worry, The equivalent to 11% very satisfying children are developing normally, it should be emphasized that not all children have the same maturity, 3% unsatisfactory, representing the children are not wearing an appropriate pace in its Socio- Affective Development.